Science Facilities. An Interpretive Bibliography - Wisconsin Univ., Madison. ERIC Clearinghouse on Educational Facilities; ERIC Clearinghouse on Educational Management ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
References pertaining to science facilities are organized and presented in the following categories--(1) biology facilities, (2) chemistry facilities, (3) physics facilities, (4) astronomy facilities, (5) elementary and secondary school science facilities, (6) college and university science facilities, and (7) planning and science laboratory. (FS)
Contract Number: OEC-1-7-070883-5095.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Science Materials; Annotated Bibliographies; Laboratory Equipment; Science Equipment; Science Facilities; Science Laboratories